Tunneling Control of Transmission Coefficient and Group Index in a Quantum Dot Nanostructure - Hamid Reza Hamedi; A. Khaledi-Nasab; H. Ghaforyan (Advances in Condensed Matter Physics)
We theoretically study the transmission and group index properties of the probe field in a four-level quantum dot molecule. It is found that the tunnel coupling plays a very important role in realizing the transmission coefficient of the probe field. Moreover, the impact of an incoherent pump field on imaginary part of susceptibility is investigated. We show that probe transmission exhibits oppositional behavior against weak and strong incoherent pump rates. This approach allows substantial flexibility in the manipulation of group velocity of light.